Pengaruh Price Bundling dan Product Bundling terhadap Niat Membeli yang Dimoderasi oleh Barang Komplementaritas - Andreas Wijaya; Loedry Kinder (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2020)
This research aim to examine the affects of price bundling, product bundling on purchase intention and complementary product as moderating variable in convenience store. Sample was taken with purposive method as much 160 sample in questionnaire survey with closed question and 5-point likert scale. the collected data was processed using SmartPLS02. As the result of hyphoteis test are H1 accepted, which means that the price bundling variable has a significant on purchase intention. H2 is accepted, which means product bundling variable has a significant on purchase intention. H3 is accepted, which means complementary product has moderating effect on on relationship of price bundling to purchase intention. H4 is rejected, which means complementary product can’t be moderating variable on relationship of product bundling to purchase intention. Based on the result, price bundling and product bundling has a signinficant effect on purchase intention.